Fate of per- and polyfluoroalkyl substances (PFAS) during hydrothermal liquefaction of municipal wastewater treatment sludge. Issue 5 (20th March 2020) - Yu, Jie; Nickerson, Anastasia; Li, Yalin; Fang, Yida; Strathmann, Timothy J.
Abstract : PFAS sorbed to sludge degrade to varying degrees when sludge is subjected to hydrothermal liquefaction for production of liquid fuel. Abstract : Hydrothermal liquefaction (HTL) is a promising technology for recovering energy from wastewater treatment sludge in the form of liquid biofuel, but there are concerns about the fate of persistent organic contaminants sorbed to the sludge. This study monitored the fate and degradation of representative per- and polyfluoroalkyl substances (PFAS) in water and sorbed to a municipal wastewater treatment sludge during HTL reactions. The yield and carbon mass content of the biocrude oil product from HTL of sludge increased with increasing reaction temperature from 260 to 300 °C and stabilized with further temperature elevation to 350 °C. Increasing temperature and reaction time also benefited PFAS transformation during the HTL process. Reaction at 350 °C for 90 min led to >99% transformation of fluorinated carboxylic acid structures (perfluorooctanoic acid, PFOA; 7:3 fluorotelomer carboxylic acid, 7:3 FTCA; and 8:2 fluorotelomer unsaturated carboxylic acid, 8:2 FTUCA), but more limited transformation was observed for sulfonic acid structures (34% degradation of perfluorooctane sulfonate, PFOS; 67% degradation of 8:2 fluorotelomer sulfonate, 8:2 FTS). Defluorination data indicates partial mineralization of PFAS during these reactions. Multiphase quantitative analysis shows that the majority of undegraded PFAS partitioned into the HTL biocrude oil product, demonstrating minimal release to the aqueous and solid products, but also indicating the need for monitoring and further purification when upgrading the biocrude oil.